Response of the GAGG(Ce) scintillator to charged particles compared with the CsI(Tl) scintillator. (12th October 2021) - Furuno, T.; Koshikawa, A.; Kawabata, T.; Itoh, M.; Kurosawa, S.; Morimoto, T.; Murata, M.; Sakanashi, K.; Tsumura, M.; Yamaji, A.
Abstract: GAGG(Ce) is a novel scintillator with a fast response and high light output without a hygroscopic nature. It is expected to be a useful detector for charged particles at high-counting rates. However, the response of the GAGG(Ce) scintillator to charged particles has not been fully examined. In the present work, the light output and energy resolution of the GAGG(Ce) scintillator were measured for protons and alpha particles at E p =5–68 MeV and E α =8–54 MeV as well as gamma rays at E γ =662 keV from a 137 Cs source. The results were compared with those of the CsI(Tl) scintillator. The scintillation efficiencies d L /d E of the GAGG(Ce) and CsI(Tl) scintillators were obtained and parametrized as a function of linear energy transfer d E /d x .